Periprosthetic joint infections are different from osteosynthesis-associated infections (Annals of Medical Research, 2021)
Aim: The aim of the study is comparing the treatment results and showing the differences between periprosthetic joint infectionsand osteosynthesis-associated infections.Materials and Methods: We retrospectively reviewed the cases of orthopedic implant-associated infections. All patients werecategorized into two groups; Group A has consisted of osteosynthesis-associated infections, and Group B has consisted ofperiprosthetic joint infection. The time interval between implantation and infection, length of hospitalization, number of operations,the status of preoperative and postoperative intensive care unit, and number of outpatient clinic applications were recorded. Culturedata from intraoperative deep tissue samples were also recorded.Results: There were 28 patients in Group A and 20 patients in Group B. The age distributions and operation numbers were significantlydifferent between the two study groups (p=0.000 and p=0.05, respectively). There was a significant difference between the numberof outpatient clinic applications and the success of treatment (p=0.016). There was a significant difference between the post-operatively intensive care unit status and success of treatment (p=0.002).Conclusion: Periprosthetic joint infection patients were older and had a higher number of operations, however orthopedic implant-associated infections were more likely outpatient clinic applications and post-operatively intensive care unit status.
Keywords: Orthopaedic implant-associated infection; osteosynthesis associated infection; prosthetic joint infection